Child Marriage: Taboo, Religion, and Women in Symbolic Violence - Jihan Fitri , Fatimatus Zahro’; Alimatul Qibtiyah; Ro’fah (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Child marriage is a phenomenon that still occurs in Indonesia. The occurrence of child marriage is inseparable from the role of parents and the weak position of girls in the family. The phenomenon of child marriage indirectly affects women's subordination. In this regard, religion and taboos have a role in perpetuating child marriage, reproducing subordination, and symbolic violence against women. This research is qualitative research with an anthropological sociology approach. The focus of the research is toanalyze the influence of taboo and religion on the role and negotiation of women in the process of child marriage. The results of the study state that a disproportionate understanding of Islamic teachings reinforces taboos and supports the practice of child marriage, thereby reproducing symbolic violence and subordination against women.